"It's not about me, it's about us": a narrative inquiry on living life as a social entrepreneur. Issue 3 (7th March 2020) - Jeong, Shinhee; Bailey, Jeanne M.; Lee, Jin; McLean, Gary N.
Abstract : Purpose: The purpose of this study is to help us understand social entrepreneurs' lived experiences, reflecting the comprehensive entrepreneurial processes that encompass their past, present and future. Design/methodology/approach: A narrative approach was used to explore the meaning of experiences in social entrepreneurs' professional lives through the stories retold and restructured by social entrepreneurs. A total of 11 social entrepreneurs in the Midwest region of the USA were interviewed. Findings: The authors identified three time-sequential themes: past (looking backward at the origin), present (living life as a social entrepreneur) and future (looking forward). Seven sub-themes emerged, revealing social entrepreneurs' aspiration, self-knowledge, identity-defining moments, their sustainability-oriented leadership and how they build an organizational structure, partnership and handle the burden of work and the organization. Practical implications: The findings offer useful information for future social entrepreneurs as they can learn from the perspectives of experienced social entrepreneurs in terms of what to prepare for and expect so they can achieve their full entrepreneurial potential. It can also aid in further development of social entrepreneur curricula in business and non-business schools. Originality/value: The existing literature does not portray sufficient detail about how social entrepreneurs live the lives they have created and chosen to understand their lived experiences. This study also provides a comprehensive definition of social entrepreneurship, incorporating "collective perspective" with a mentality of "it's not about me, it's about us".